An information processing approach to the assessment and remediation of developmental dyslexia - Broom, Yvonne Margaret (My University, 1992)
Remediation programmes were devised and implemented for two developmental dyslexics. Extensive pre-therapy psycholinguistic assessment determined the developmental stage at which their acquisition of reading skills had arrested. [Abbreviated abstract. Open document to view full version]
A Dissertation Submitted to the Faculty of Arts University of the Witwatersrand, Johannesburg for the Degree of Master of Arts Johannesburg 1991
Keywords: Dyslexia; Reading disability